Gonzalo Correas' ocabulario de refranes y frases proverbiales - Hernando García-Cervigón, Alberto (Boletín de Filología, 2009)
Despite the ups and downs gone through by its original manuscriptbefore Louis Combert's published it during the sixties of the lastcentury, Gonzalo Correa`s Vocabulary of Sayings and ProverbialPhrases constitutes a real monument in the fi eld of Hispanic philologyby its linguistic documentary wealth. Written in the author's phoneticspelling at a time when the changes in the consonantal subsystem hadpractically reached completion, this valuable document allows theresearcher to carry out a rigorous study of one of the most peculiarfeatures of the Spanish language, i.e. that concerning the daily lifemetaphors as they are refl ected in sayings and proverbial phrases, awealth of thought and customs amassed in these expressions sincethe beginnings of the language to the present, which if not presentin the current speech it is at least well enough documented in theSpanish literary production of the last centuries.